2015
DOI: 10.1002/advs.201500257
|View full text |Cite
|
Sign up to set email alerts
|

Novel Piezoelectric Paper‐Based Flexible Nanogenerators Composed of BaTiO3 Nanoparticles and Bacterial Cellulose

Abstract: A piezoelectric paper based on BaTiO3 (BTO) nanoparticles and bacterial cellulose (BC) with excellent output properties for application of nanogenerators (NGs) is reported. A facile and scalable vacuum filtration method is used to fabricate the piezoelectric paper. The BTO/BC piezoelectric paper based NG shows outstanding output performance with open‐circuit voltage of 14 V and short‐circuit current density of 190 nA cm−2. The maximum power density generated by this unique BTO/BC structure is more than ten tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 34 publications
1
99
1
Order By: Relevance
“…The rise-time of the electromotive force is related to the shock front propagation time through the ferroelectric sample thickness (Shkuratov et al 2010). Values of functional parameters (generated voltage, current, and power) of cellulose/SbSI nanogenerators presented in this article are hard to compare to data reported for piezoelectric papers (Kumar et al 2011;Liao et al 2014;Zhang et al 2016). Different researchers applied various excitation methods (i.e., bending, pressing, and ultrasonic waves).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The rise-time of the electromotive force is related to the shock front propagation time through the ferroelectric sample thickness (Shkuratov et al 2010). Values of functional parameters (generated voltage, current, and power) of cellulose/SbSI nanogenerators presented in this article are hard to compare to data reported for piezoelectric papers (Kumar et al 2011;Liao et al 2014;Zhang et al 2016). Different researchers applied various excitation methods (i.e., bending, pressing, and ultrasonic waves).…”
Section: Resultsmentioning
confidence: 89%
“…This paper had the largest piezoelectric coefficient, d 33 = 4.8(4) 9 10 -12 C/N, at the highest nanoparticle loading of 48 wt% BaTiO 3 . Paper-based piezoelectric generator made of bacterial cellulose and BaTiO 3 was presented by Zhang et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other doping mechanisms, including the use of metallic inclusions, such as silver nanoparticles have also been reported [104]. Furthermore, future research of this field will benefit from progress in the discovery of new piezoelectric polymeric systems and crystalline phases, both synthetic and natural, that may find use in both piezoelectric and triboelectric energy harvesters, Cellulose, for example, is an abundant and common natural polymer can be found from cell walls of green plants, and it has recently been incorporated as piezo-or tribo-active materials for energy harvesting applications [105][106][107][108]. It is clear that advances in nanofabrication of polymeric materials and devices will likely continue to drive the field forward, particularly through precise control and/or enhancement of their relevant properties at the nanoscale.…”
Section: Discussionmentioning
confidence: 99%
“…At such rates, it is not a facile task to achieve homogeneous dispersions, but it is more likely to see the formation of the agglomeration which can behave as a defect site, leading to a greater reduction of dielectric properties. Published studies [18,19,20,21] have revealed that localized electric fields are created within the matrix with field exclusion. For example, the addition of (5%–10% v/v) BaTiO 3 nanoparticles generates local electrical fields which negatively affect dielectric properties [20,21].…”
Section: Introductionmentioning
confidence: 99%